Gender differentiation in tactical options in defense and attack on beach handball - Konstantinos Gkagkanas; Dimitris Hatzimanouil; Vasilis Skandalis (Exercise and Quality of Life)
Although beach handball comes from the sport that is played indoors it has significant differences from it. The aim of the study was to investigate and compare tactical options in both defense and attack between men and women. In 16 games from 2017 European Beach Handball Championship, 1074 attacks and defense situations were analyzed, in order to examine different attack and defense tactics. The selected method was video-analysis. The ꭓ2-test was used to compare the differences between the formations in defense and attack. In defense the results showed that men use more often 3:0, 2:1C and 2:1L formations, while women use more often 3:0. From the comparison between men and women it appeared that, in the initial formation of defense, there are significant differences, while in the final tactical formation are minimal. Men, in the initial and final tactical option in attack, used the system with one pivot and the specialist in center. Women use the same formation but also the one with a pivot and specialist at the left side of the attack at the substitution area. In the initial attack formation, appeared few significant changes between men and women, while in the final tactical formation there were no changes. Finally, the final throwing attempts, men choose to make them mainly from the center while women from the right and from the center. In conclusion, we can say that men’s and women’s tactical choices in defense and offense show some differences, but these differences are small.